Budget Politics, Motivation, In Budget Participation, And Local Government Performance In Indonesia - Usman, Ernawaty; Sugianto, Sugianto; Usman, Asri (LPPM ISNJ Bengkalis, 2024)
This study investigates the impact of budget participation on the performance of local government agencies, exploring the mediating role of motivation and the moderating effect of budget politics. This study used an explanatory design and data collection through surveys from a population of 14,144 state civil servants involved in the budgeting process across 514 districts and cities in Indonesia, with a valid sample of 254. The results show that higher levels of participation and motivation in the budgeting process can enhance the performance of local government officials. Motivation mediates the relationship between budget participation and performance, suggesting that increased participation boosts performance through improved motivation. Furthermore, budget politics strengthens the effect of participation on motivation. The theoretical contributions of this study reinforce goal-setting theory and agency theory. Practical implications emphasize fostering greater budget participation by boosting employee motivation to improve performance. Local governments should aim to design more inclusive budgeting processes and consider political dynamics, as they can amplify the positive effects of participation. Additionally, implementing training and motivational programs can optimize the budgeting process and further improve the effectiveness of local governments.